Radio signatures of magnetic restructuring during the 2000 July 14 major solar event - Caroubalos, C.; Tsitsipis, P.; Kontogeorgos, A.; Moussas, X.; Alissandrakis, C. E.; Hillaris, A.; Preka-Papadema, P.; Polygiannakis, J.; Bougeret, J. -L.; Dumas, G.; Kurt, V.; Vassiliou, C.; et al. (2002)
We analyse the fine structure of the type IV radio burst, during the main phase of the 14th July 2000 major event recorded by the radiospectrograph ARTEMIS-IV, in the 110-650 MHz (10 Hz sampling rate) and the 270-450 MHz (100 Hz rate) range. In this report we focus on variations in frequency drift rate and repetition rate of fibers bursts. A pronounced asymmetry between the number of bursts with positive and negative frequency drift is noted at certain time periods. These variations follow closely the evolution of the magnetic structure associated with the major solar event and the onset of the corresponding CME.
Keywords: Coronal Mass Ejection; Fine Structure; Solar Radio Bursts